1990
DOI: 10.1302/0301-620x.72b4.2380231
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the trapezius for flail shoulder after brachial plexus injury

Abstract: Shoulder arthrodesis is often used to treat flail shoulder after a brachial plexus injury, but has a high complication rate and entails loss of passive mobility. We have reviewed 27 patients with brachial plexus injury treated by transfer of the trapezius to the proximal humerus at an average time from injury of 31.3 months. Pre-operatively, all 27 shoulders were subluxated, with an average abduction of 3.5 degrees. Postoperatively, shoulder abduction averaged 45.4 degrees, and subluxation was abolished. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
5

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 13 publications
1
43
0
5
Order By: Relevance
“…Bateman (1955) described the transfer with acromion osteotomy and other experiences were later published by several authors (Saha 1967, Karev 1986, Aziz et al 1990, I s t v h 1993.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bateman (1955) described the transfer with acromion osteotomy and other experiences were later published by several authors (Saha 1967, Karev 1986, Aziz et al 1990, I s t v h 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Most were initially described for treatment of paralysis after poliomyelitis (Mayer 1927, Harmon 1950, Saha 1967. In recent years, some authors have reported their good experience with trapezius muscle transfer for the paralytic shoulder after brachial plexus injuries (Karev 1986, Aziz et al 1990, Istvh et al 1993.…”
mentioning
confidence: 99%
“…5 The surgical technique was initially described by Mayer (1927), 18 who also used a fascia lata plasty to increase the length of the trapezius insertion. Bateman (1955) 11 described the transfer with acromion osteotomy and other experiences were later published by several authors (Saha 1967, 5 Karev 1986, 10 Aziz et al 1990 9 ). To achieve the necessary tension in trapezius transfer, the fixation of the acromial fragment is done as far as distal on the humerus as possible.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,5 In recent years, some authors have reported their good experience with trapezius muscle transfer for the paralytic shoulder after brachial plexus injuries. 9,10 In this study, we evaluated the results of the trapezius transfer for reconstruction of shoulder motion in adult patients with longstanding traumatic brachial plexus injuries.…”
Section: How To Cite This Articlementioning
confidence: 99%
“…The requirements for transfer are as follows: passive shoulder abduction to 80°, patient agreement regarding the long immobilization time, and satisfactory preoperative condition of the glenohumeral joints. If these requirements are not met, shoulder arthrodesis must be performed in the functional position, which carries a higher risk of morbidity and is considered the last resort 7,8,11 . Satisfactory results have been reported with regard to the use of the modified Burkhalter transfer for the correction of triple paralysis of the radial nerve 13 .…”
Section: Discussionmentioning
confidence: 99%